Analysis of Marketing Strategies to Increase Sales at PT. Karya Tunggal Properti - Effendy, Aidil Amin (Universitas Negeri Makassar, 2018)
Innovative and creative marketing strategies must always be carried out so that the company does not experience a loss in sales so that if it is unable to compete with other companies. The purpose of this study was to determine the implementation of the marketing strategy of PT. Karya Tunggal Properti Pamulang Tangerang Selatan and know the implementation of the marketing strategy of PT. Karya Tunggal Properti Pamulang, Tangerang Selatan to increase sales. In this study, the research approach used is to use qualitative methods. Qualitative research is aimed at gaining a deep understanding of the situation at hand. In this study, data collection techniques used in qualitative methods are interviews, observation, and documentation. The research results obtained, namely in general property products managed by PT. Karya Tunggal Properti experienced sales growth from year to year, but the target of the company has not been achieved. The unit sales data obtained are a total of 20 housing units sold from 2017 totaling 8 units and in 2018 totaling 12 units, while the target given by the company is 36 units so that the realization of the percentage obtained only reaches 22.22% and 33.33 %, but sales from 2017 to 2018 increased by 11.11%. The success of increasing sales of PT. Karya Tunggal Properti for 1 year was obtained from the implementation of marketing strategies, including product strategy, price, promotion, and place.